2021
DOI: 10.1186/s13071-021-04646-0
|View full text |Cite
|
Sign up to set email alerts
|

Masting by beech trees predicts the risk of Lyme disease

Abstract: Background The incidence of Lyme borreliosis and other tick-borne diseases is increasing in Europe and North America. There is currently much interest in identifying the ecological factors that determine the density of infected ticks as this variable determines the risk of Lyme borreliosis to vertebrate hosts, including humans. Lyme borreliosis is caused by the bacterium Borrelia burgdorferi sensu lato (s.l.) and in western Europe, the hard tick Ixodes ricinus is the most important vector. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 103 publications
3
46
1
Order By: Relevance
“…Thus, for each climate variable, there were a total of 12 seasonal means (3 years * 4 seasons per year = 12) and 3 annual means. The exception was the annual snow fall (units of cm) which was calculated over the time from October 1 (e.g., previous year) to May 31. Annual beech masting score: Previous studies have shown that there is a 2-year time lag between masting events and the annual DON and the annual DIN [12,14,35,36]. Our recent analyses of the same data showed that inter-annual variation in the DON and the DIN was strongly associated with the mast scores 2 years prior of European beech but not Norway spruce [12,36].…”
Section: Weather On the Day Of Tick Samplingmentioning
confidence: 72%
See 3 more Smart Citations
“…Thus, for each climate variable, there were a total of 12 seasonal means (3 years * 4 seasons per year = 12) and 3 annual means. The exception was the annual snow fall (units of cm) which was calculated over the time from October 1 (e.g., previous year) to May 31. Annual beech masting score: Previous studies have shown that there is a 2-year time lag between masting events and the annual DON and the annual DIN [12,14,35,36]. Our recent analyses of the same data showed that inter-annual variation in the DON and the DIN was strongly associated with the mast scores 2 years prior of European beech but not Norway spruce [12,36].…”
Section: Weather On the Day Of Tick Samplingmentioning
confidence: 72%
“…Given the importance of I. ricinus as a disease vector, forecasting the density of ticks questing for hosts is important for managing the risk of tick-borne diseases [12,13,35,36,[69][70][71]. In Europe, there is much interest to determine which ecological factors are influencing the seasonal and inter-annual abundance of I. ricinus ticks [12,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, forecasts of seed and fruit crops in New Zealand inform both the management of invasive mammals and translocation programmes of the endangered kakapo [ 95,96]. Similarly, the effect of masting on zoonotic, tick-borne disease incidents in human populations, driven by the effect of cycling rodent populations on tick numbers, can be forecast with a time horizon of up to 2 years [97]. In other cases, where forecasts of seed and fruit crops are not made, interannual variation in seed crops is an obstacle to environmental management.…”
Section: (E) Applicationsmentioning
confidence: 99%